A fixação das crenças à luz da dialogia semiótica de Charles Sanders Peirce - Bittencourt, Renata (2014)
Over time, the beliefs are modified according to the cultural and historical development that determines the life of men. They are consolidated by training conditions of communities on the one hand, and personal opinions and different tastes, on the other. The theme of this dissertation will be addressed by checking the possibilities of fixing beliefs as the four methods suggested by Charles S. Peirce: Belief by tenacity, belief in authority, a priori belief and scientific belief. This theme offers unique opportunities for reflection, so we bring Semiotics as a reading of the four methods mentioned tool. We will use the concepts of continuity and dialogic truncation of signs, and we intend to prove that the maintenance of trade signs favors the growth of knowledge, avoiding some forms of dogmatism. Article "The Fixation of Belief "(1877) Peirce will be analyzed so that we can understand the methods of fixing beliefs. Also, we make a study on the relation of the beliefs and the signs that these shapes are formed and developed. Finally, we address the article by Ivo Ibri " Choices, dogmatism and Betting" (2012), whose conceptual axis brings us a reflection on the realism of Peirce , trying to show it as a principle from which many of his philosophical doctrines are derivatives